Translation and cross-cultural adaptation of a questionnaire for assessing hyperacusis in Williams syndrome - Nascimento, Jacqueline Aquino do; Mielle, Lucas Pinto; Silva, Liliane Aparecida Fagundes; Samelli, Alessandra Giannella; Matas, Carla Gentile (Arquivos de Neuro-Psiquiatria, 2025)
Williams syndrome (WS) is a genetic, multisystemic, and neurodevelopmental disorder. The prevalence of auditory hypersensitivity in WS is high, especially in childhood, with reports in the literature from 94 to 100% of individuals evaluated, which can generate significant impacts on their quality of life. Therefore, the existence of instruments for screening hyperacusis that are easy and quick to apply for use in clinical routine is essential.To translate and perform the cross-cultural adaptation of the Hyperacusis Screening Questionnaire into Brazilian Portuguese.A questionnaire concerning auditory hypersensitivity in WS was translated by two translators who are fluent in English. After the synthesis of the translations, back-translation was performed to analyze similarity, a meeting of the expert committee for semantic and linguistic adaptation of the instrument was held, and pretesting and validation of content and appearance was conducted.The translated and adapted version of the questionnaire was similar to the original regarding general and referential meaning. Answers from 324 families of individuals with WS were included, 85.2% of those reported hyperacusis as a ongoing symptom.The translation and cross-cultural adaptation of the questionnaire were performed according to the methodology recommended in the literature, with necessary equivalences being made for the Brazilian reality. The instrument developed and tested in the present study proved to be useful in screening for hyperacusis in the population with WS, allowing its use in future investigations on the subject and comparison with other studies.
Keywords: Williams Syndrome; Hyperacusis; Audiology; Translating; Surveys and Questionnaires